JP2000290500A - Polyamide molding - Google Patents
Polyamide moldingInfo
- Publication number
- JP2000290500A JP2000290500A JP10003999A JP10003999A JP2000290500A JP 2000290500 A JP2000290500 A JP 2000290500A JP 10003999 A JP10003999 A JP 10003999A JP 10003999 A JP10003999 A JP 10003999A JP 2000290500 A JP2000290500 A JP 2000290500A
- Authority
- JP
- Japan
- Prior art keywords
- polyamide
- parts
- molded product
- weight
- layered silicate
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Pending
Links
Landscapes
- Manufacture Of Macromolecular Shaped Articles (AREA)
- Laminated Bodies (AREA)
- Shaping By String And By Release Of Stress In Plastics And The Like (AREA)
- Compositions Of Macromolecular Compounds (AREA)
Abstract
(57)【要約】
【課題】 本発明は、包装資材して要求される透明性、
ガスバリヤー性、機械的性能に優れたポリアミド成形物
を提供することを目的とする。
【解決手段】 ジアミン成分中にメタキシリレンジアミ
ンを70モル%以含むジアミンと、ジカルボン酸成分中
に炭素数4〜20のα,ω−直鎖脂肪族カルボン酸を7
0モル%以上含むジカルボン酸とを重縮合したポリアミ
ド樹脂A)100重量部に対し、層状珪酸塩(B)を
0.1〜10重量部配合して得れる樹脂組成物(C)を
成形したポリアミド成形物であって、層状珪酸塩が溶混
練によりポリアミド樹脂中に微分散されていることを特
徴とするポリアミド形物。(57) [Summary] [PROBLEMS] The present invention provides transparency required for packaging materials,
An object of the present invention is to provide a polyamide molded article having excellent gas barrier properties and mechanical performance. SOLUTION: A diamine containing 70 mol% or less of meta-xylylenediamine in a diamine component, and an α, ω-linear aliphatic carboxylic acid having 4 to 20 carbon atoms in a dicarboxylic acid component are contained in 7 parts.
A resin composition (C) obtained by blending 0.1 to 10 parts by weight of a layered silicate (B) with respect to 100 parts by weight of a polyamide resin A) obtained by polycondensation with a dicarboxylic acid containing 0 mol% or more was molded. A polyamide molded product, characterized in that a layered silicate is finely dispersed in a polyamide resin by melt-kneading.
Description
【0001】[0001]
【発明の属する技術分野】本発明は、食品、飲料、薬
品、電子部品等の包装資材として透明性、ガスバリヤー
性、機械的性能に優れたポリアミド成形物に関するもの
である。BACKGROUND OF THE INVENTION 1. Field of the Invention The present invention relates to a polyamide molded article excellent in transparency, gas barrier properties and mechanical performance as a packaging material for foods, beverages, medicines, electronic parts and the like.
【0002】[0002]
【従来の技術】キシリレンジアミンと脂肪族ジカルボン
酸との重縮合反応から得られるポリアミド、例えばメタ
キシリレンジアミンとアジピン酸から得られるポリアミ
ドMXD6(以下「MXナイロン」という場合がある)
は、酸素、炭酸ガス等のガス状物質に対する低い透過性
を示すことから、ガスバリヤー材料としてフィルム、ボ
トルとして利用されている。ただし、近年、食品や飲料
等の鮮度を損なわずに長期間保存するためのガスバリヤ
ー包装の必要性はさらに高まっており、より一層のガス
バリヤー性向上が要求されている。2. Description of the Related Art A polyamide obtained from a polycondensation reaction between xylylenediamine and an aliphatic dicarboxylic acid, for example, a polyamide MXD6 (hereinafter sometimes referred to as "MX nylon") obtained from meta-xylylenediamine and adipic acid.
Because of its low permeability to gaseous substances such as oxygen and carbon dioxide, it is used as a film or bottle as a gas barrier material. However, in recent years, the necessity of gas barrier packaging for preserving foods and beverages for a long period of time without deteriorating freshness has been further increased, and further improvement in gas barrier properties is required.
【0003】ポリアミド樹脂のガスバリヤー性を改良す
る方法の一つとして、ポリアミド樹脂中に層状珪酸塩を
添加させる方法がある。特公昭58−35211号公
報、特開平2−105856号公報等では、予め層状珪
酸塩を膨潤させた後、ポリアミド−6の原料であるε−
カプロラクタムと混合し重合を行うことで、層状珪酸塩
をポリアミド−6中に均一に分散させる方法が開示され
ている。この方法によりポリアミド−6のガスバリヤー
性は向上するものの、層状珪酸塩添加後の溶融粘度が上
昇するため、重合缶からのポリマーの抜き出しが困難と
なることが懸念される。One of the methods for improving the gas barrier properties of a polyamide resin is to add a layered silicate to the polyamide resin. In Japanese Patent Publication No. 58-35211 and JP-A-2-105856, etc., after the layered silicate is swollen in advance, the ε-
A method is disclosed in which a layered silicate is uniformly dispersed in polyamide-6 by mixing and polymerizing with caprolactam. Although the gas barrier property of the polyamide-6 is improved by this method, the melt viscosity after the addition of the layered silicate increases, so that there is a concern that it is difficult to extract the polymer from the polymerization can.
【0004】[0004]
【発明が解決しようとする課題】本発明は、ポリアミド
樹脂中に層状珪酸塩を微分散させることで、包装資材と
して要求される透明性、ガスバリヤー性、機械的性能に
優れたポリアミド成形物を提供しようとするものであ
る。DISCLOSURE OF THE INVENTION The present invention provides a polyamide molded article excellent in transparency, gas barrier property and mechanical performance required as a packaging material by finely dispersing a layered silicate in a polyamide resin. It is something to offer.
【0005】[0005]
【課題を解決するための手段】本発明者らは、上記目的
を達成するため鋭意検討した結果、特定構造のポリアミ
ド樹脂と層状珪酸塩とを溶融混練することで、上記の問
題を解決し得ることを見いだし、本発明を完成するに到
った。Means for Solving the Problems The inventors of the present invention have made intensive studies to achieve the above object, and as a result, the above-mentioned problems can be solved by melt-kneading a polyamide resin having a specific structure and a layered silicate. This led to the completion of the present invention.
【0006】すなわち、本発明は、ジアミン成分中にメ
タキシリレンジアミンを70モル%以上含むジアミン
と、ジカルボン酸成分中に炭素数4〜20のα,ω−直
鎖脂肪族ジカルボン酸を70モル%以上含むジカルボン
酸とを重縮合したポリアミド樹脂(A)100重量部に
対し、層状珪酸塩(B)を0.1〜10重量部配合して
得られる樹脂組成物(C)を成形したポリアミド成形物
であって、層状珪酸塩が溶融混練によりポリアミド樹脂
中に微分散されていることを特徴とするポリアミド成形
物に関する発明である。That is, the present invention relates to a diamine containing 70% by mole or more of metaxylylenediamine in a diamine component and 70 moles of an α, ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms in a dicarboxylic acid component. % Of a polyamide resin obtained by blending 0.1 to 10 parts by weight of a layered silicate (B) with respect to 100 parts by weight of a polyamide resin (A) polycondensed with a dicarboxylic acid containing at least 10% by weight. The invention relates to a molded article, wherein the layered silicate is finely dispersed in a polyamide resin by melt-kneading.
【0007】本発明で使用するポリアミド樹脂(A)と
は、原料ジアミン成分中にメタキシリレンジアミンを7
0モル%以上含むジアミンと、原料ジカルボン酸成分中
に炭素数4〜20のα,ω−直鎖脂肪族ジカルボン酸を
70モル%以上含むジカルボン酸から重縮合して得られ
るポリアミド樹脂である。当該ポリアミド樹脂は実用的
には結晶性ポリアミド樹脂である。[0007] The polyamide resin (A) used in the present invention means that metaxylylenediamine is contained in the starting diamine component.
It is a polyamide resin obtained by polycondensation of a diamine containing 0 mol% or more and a dicarboxylic acid containing 70 mol% or more of α, ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms in a raw material dicarboxylic acid component. The polyamide resin is practically a crystalline polyamide resin.
【0008】ここで結晶性ポリアミドとは、例えばナイ
ロン6やナイロン66のように融点を有する結晶性高分
子であり、結晶化度、結晶化度分布、結晶の集合体であ
る球晶の大きさ、およびその分布状態により、ポリアミ
ド樹脂成形品の物性、比重、寸法安定性等に影響を及ぼ
す。例えばこれらの結晶性ポリアミドは延伸によって分
子を配向結晶化させ、強度を高めることができる。本発
明で使用するポリアミド(A)も融点を有し、結晶系ポ
リアミドとしての性質を示すことから、本発明のフィル
ム、中空容器等の材料として有用である。Here, the crystalline polyamide is a crystalline polymer having a melting point, such as nylon 6 or nylon 66, and has a crystallinity, a crystallinity distribution, and a size of a spherulite which is an aggregate of crystals. , And its distribution affect the physical properties, specific gravity, dimensional stability and the like of the polyamide resin molded article. For example, these crystalline polyamides can be oriented and crystallized by stretching to increase the strength. Since the polyamide (A) used in the present invention also has a melting point and exhibits properties as a crystalline polyamide, it is useful as a material for the film, hollow container and the like of the present invention.
【0009】本発明において、ポリアミド(A)の原料
ジアミンは、メタキシリレンジアミンを70モル%以上
含むものである。また、本発明において、メタキシリレ
ンジアミン中に他のジアミンとして、テトラメチレンジ
アミン、ペンタメチレンジアミン、ヘキサメチレンジア
ミン、オクタメチレンジアミン、ノナメチレンジアミン
等の脂肪族ジアミン、パラフェニレンジアミン、メタキ
シリレンジアミン、パラキシリレンジアミン等の芳香族
ジアミン、ビス(アミノメチル)シクロヘキサン等の脂
環族ジアミン類等を全ジアミン成分中に30モル%未満
の範囲で使用することができる。In the present invention, the starting diamine of the polyamide (A) contains at least 70 mol% of metaxylylenediamine. Further, in the present invention, other diamines in meta-xylylenediamine, such as aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, octamethylenediamine, nonamethylenediamine, paraphenylenediamine, metaxylylenediamine And aromatic diamines such as para-xylylenediamine and alicyclic diamines such as bis (aminomethyl) cyclohexane can be used in an amount of less than 30 mol% in all diamine components.
【0010】本発明において、ポリアミド(A)の原料
のジカルボン酸成分である炭素数4〜20のα,ω−直
鎖脂肪族ジカルボン酸として、例えばコハク酸、グルタ
ル酸、ピメリン酸、スベリン酸、アゼライン酸、アジピ
ン酸、セバシン酸、ウンデカン二酸、ドデカン二酸等の
脂肪族ジカルボン酸が例示できるが、これら中でもアジ
ピン酸が好ましい。上記α,ω−直鎖脂肪族ジカルボン
酸中にテレフタル酸、イソフタル酸、2,6−ナフタレ
ンジカルボン酸等の芳香族ジカルボン酸類等を全ジカル
ボン酸成分中に30モル%未満含むものでも使用するこ
とができる。In the present invention, as the dicarboxylic acid component of the raw material of the polyamide (A), as the α, ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms, for example, succinic acid, glutaric acid, pimelic acid, suberic acid, Aliphatic dicarboxylic acids such as azelaic acid, adipic acid, sebacic acid, undecandioic acid and dodecanedioic acid can be exemplified, and among these, adipic acid is preferred. The above α, ω-linear aliphatic dicarboxylic acids may contain aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, etc., in a total dicarboxylic acid component of less than 30 mol%. Can be.
【0011】ポリアミド樹脂(A)が原料ジアミン成分
中にメタキシリレンジアミンを70モル%以上含み、原
料ジカルボン酸成分中に炭素数4〜20のα,ω−直鎖
脂肪族ジカルボン酸を70モル%以上含む原料から重縮
合して得たものである場合は、最終的にフィルム、シー
ト、中空容器としたときの酸素、炭酸ガス等のガス状物
質に対する遮断性等の特性が優れる。The polyamide resin (A) contains 70 mol% or more of metaxylylenediamine in the starting diamine component and 70 mol of α, ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms in the starting dicarboxylic acid component. % Or more, it is excellent in properties such as barrier properties against gaseous substances such as oxygen and carbon dioxide when finally formed into films, sheets and hollow containers.
【0012】本発明において、ポリアミド樹脂(A)の
相対粘度は2.2〜4.0が好ましく、2.4〜3.7
がさらに好ましい。相対粘度が2.2〜4.0のポリア
ミド(A)を使用することで、最終的にフィルム、シー
ト、中空容器にする際の成形性が良好となる。In the present invention, the relative viscosity of the polyamide resin (A) is preferably from 2.2 to 4.0, preferably from 2.4 to 3.7.
Is more preferred. By using a polyamide (A) having a relative viscosity of 2.2 to 4.0, the moldability when finally forming a film, sheet, or hollow container is improved.
【0013】本発明において、ポリアミド(A)と層状
珪酸塩(B)を溶融混練する方法については特に制限は
ないが、ポリアミド樹脂の溶融重合中に層状珪酸塩
(B)を添加し攪拌する方法、単軸もしくは二軸押出機
等の通常用いられる種々の押出機を用いて溶融混練する
方法等が挙げられる。なかでも、生産性、汎用性等の点
から押出機を用いる方法が好ましい。また、本発明にお
いてポリアミド樹脂(A)と層状珪酸塩(B)との溶融
混練は、例えばペレットと粉末のような固体同士をその
まま混合して押出機に投入し、Tダイを通じてシートあ
るいはフィルムを製膜する一般にドライブレンドと呼ば
れている方法、もしくは固体同士を一度溶融押しだし
し、再ペレット化したものを原料として用いる一般にメ
ルトブレンドと呼ばれている方法のいずれも行うことが
可能である。尚、ドライブレンド法の方が熱履歴が少な
く、熱劣化による機械的性能等の性能低下を小さくでき
ることから好ましい。In the present invention, the method of melt-kneading the polyamide (A) and the layered silicate (B) is not particularly limited, but a method of adding and stirring the layered silicate (B) during the melt polymerization of the polyamide resin. And a method of melt-kneading using various commonly used extruders such as a single-screw or twin-screw extruder. Among them, a method using an extruder is preferable from the viewpoint of productivity, versatility, and the like. Further, in the present invention, the melt kneading of the polyamide resin (A) and the layered silicate (B) is carried out, for example, by mixing solids such as pellets and powders as they are, putting the mixture into an extruder, and forming a sheet or film through a T-die. Either a method generally called dry blending for forming a film, or a method generally called melt blending in which solids are melted and extruded once and then repelletized as a raw material can be used. Note that the dry blend method is preferable because it has a small heat history and can reduce performance deterioration such as mechanical performance due to thermal deterioration.
【0014】本発明において、ポリアミド(A)中に含
有される層状珪酸塩(B)は局所的に凝集することなく
均一に分散している必要がある。ここでいう分散とは、
ポリアミド中において層状珪酸塩が平板状に分離し、そ
れらの50%以上が50オングストローム以上の層間距
離を有することをさす。この層間距離とは平板状物の重
心間距離をいう。この距離が大きい程分散状態が良好と
なり、最終的にフィルム、シート、中空容器としたとき
の透明性等の外観が良好で、かつ酸素、炭酸ガス等のガ
ス状物質に対する遮断性を向上させることができる。In the present invention, the layered silicate (B) contained in the polyamide (A) needs to be uniformly dispersed without local aggregation. The variance here is
It means that the layered silicate separates into a plate shape in the polyamide, and that 50% or more of them have an interlayer distance of 50 angstroms or more. The interlayer distance refers to the distance between the centers of gravity of the flat objects. The longer this distance is, the better the dispersion state is, the better the appearance such as transparency when finally made into a film, sheet, or hollow container, and the better the barrier property against gaseous substances such as oxygen and carbon dioxide gas. Can be.
【0015】本発明で使用する層状珪酸塩(B)として
は、四面体層一枚と八面体層一枚とからなる1:1型層
状珪酸塩、即ち、カオリナイト、ハロイサイト、クリソ
タイル等や、四面体層二枚と八面体層一枚とからなる
2:1型層状珪酸塩、即ち、モンモリロナイト、ヘクト
ライト、バイデライト、サボナイト等のスメクタイト
類、マスコバイト、フロゴバイト等のマイカ類、タル
ク、パイロフィライト、バーミキュライト、クロライト
等が挙げられる。これらの層状珪酸塩としては、高分子
化合物、有機系化合物、無機系化合物等の膨潤化剤と予
め接触させて層間を拡げたものを用いても良い。The layered silicate (B) used in the present invention includes a 1: 1 type layered silicate composed of one tetrahedral layer and one octahedral layer, that is, kaolinite, halloysite, chrysotile, and the like. 2: 1 type layered silicate composed of two tetrahedral layers and one octahedral layer, ie, smectites such as montmorillonite, hectorite, beidellite, savonite, mica such as muscobite, phlogovite, talc, pyrophyllite Light, vermiculite, chlorite and the like. As these layered silicates, those obtained by previously contacting a swelling agent such as a polymer compound, an organic compound or an inorganic compound to expand the interlayer may be used.
【0016】本発明における層状珪酸塩(B)の添加量
は、ポリアミド樹脂(A)100重量部に対し、0.1
〜10重量部が好ましく、0.5〜8重量部がさらに好
ましい。層状珪酸塩(B)の添加量が上記0.1重量部
以上であれば、ガスバリヤー性の向上効果が現れ、上記
10重量部以下であれば、透明性を損なうことはない。The amount of the layered silicate (B) used in the present invention is 0.1 parts by weight based on 100 parts by weight of the polyamide resin (A).
It is preferably from 10 to 10 parts by weight, more preferably from 0.5 to 8 parts by weight. When the addition amount of the layered silicate (B) is 0.1 parts by weight or more, the effect of improving gas barrier properties is exhibited, and when the addition amount is 10 parts by weight or less, transparency is not impaired.
【0017】本発明におけるポリアミド樹脂(A)と層
状珪酸塩(B)との混合物(C)からなるポリアミド成
形物とは、食品、飲料、薬品、電子部品等の包装資材と
なる成形物で、フィルム、シートやボトル状、カップ
状、トレイ状、タンク状等の中空容器等が挙げられる。In the present invention, the polyamide molded product comprising the mixture (C) of the polyamide resin (A) and the layered silicate (B) is a molded product which becomes a packaging material for foods, beverages, chemicals, electronic parts and the like. Examples include hollow containers such as films, sheets, bottles, cups, trays, and tanks.
【0018】本発明におけるポリアミド成形物の製造方
法には特に制限はないが、Tダイ押出成形、ブロー成形
等の溶融成形法が好ましい。具体的には、Tダイ押出機
を用いて未延伸フィルム、シートを製造する方法、該シ
ートを縦方向及び/又は横方向に延伸することで延伸フ
ィルムを製造する方法、該シートから深絞り成形機にて
カップ、トレイ等を製造する方法、射出成形機、あるい
は押出機を用いて円筒状パリソンを成形し、該パリソン
をブロー成形することでボトル、タンク等を製造する方
法等が挙げられるが、これらの方法に限られるものでは
ない。The method for producing a polyamide molded product in the present invention is not particularly limited, but a melt molding method such as T-die extrusion molding and blow molding is preferred. Specifically, a method for producing an unstretched film and a sheet using a T-die extruder, a method for producing a stretched film by stretching the sheet in the machine direction and / or the transverse direction, and deep drawing from the sheet A method of manufacturing a cup, tray, etc., an injection molding machine, or a cylindrical parison using an extruder, and a method of manufacturing a bottle, a tank, etc. by blow molding the parison. However, the present invention is not limited to these methods.
【0019】本発明において、混合物(C)からなる延
伸フィルムは、面積延伸倍率が4〜16倍に延伸された
ものが好ましい。面積延伸倍率を4倍以上とすることで
機械的性能が向上し、16倍以下とすることで延伸破断
することなく安定的に製造できる。In the present invention, the stretched film comprising the mixture (C) is preferably stretched to have an area stretching ratio of 4 to 16 times. When the area stretching ratio is 4 times or more, the mechanical performance is improved, and when the area stretching ratio is 16 times or less, the film can be stably manufactured without stretching and breaking.
【0020】本発明において、混合物(C)からなるボ
トルは、面積延伸倍率が1〜30倍に延伸ブローされた
ものが好ましい。面積延伸倍率を30倍以下とすること
で延伸破断することなく安定的に製造できる。In the present invention, it is preferable that the bottle comprising the mixture (C) is stretch-blown at an area stretching ratio of 1 to 30 times. By setting the area stretching ratio to 30 times or less, it is possible to stably manufacture without stretching fracture.
【0021】本発明における混合物(C)からなる少な
くとも一つの層と、他の熱可塑性樹脂からなる少なくと
も一つの層が接合してなるポリアミド成形物とは、食
品、飲料、薬品、電子部品等の包装資材となる成形物
で、多層フィルム、多層シートやボトル状、カップ状、
トレイ状、タンク状等の多層中空容器等が挙げられる。In the present invention, a polyamide molded article obtained by joining at least one layer made of the mixture (C) and at least one layer made of another thermoplastic resin is used for a food, beverage, medicine, electronic part and the like. A molded product that serves as packaging material, and can be used in multilayer films, multilayer sheets, bottles, cups,
A multilayer hollow container such as a tray or a tank may be used.
【0022】本発明における積層体の成形方法として
は、複数のTダイ押出機を用い共押出して未延伸フィル
ム、シートを製造する方法、該シートを縦方向及び/又
は横方向に延伸することで延伸フィルムを製造する方
法、該シートから深絞り成形機にてカップ、トレイ等を
製造する方法、複数の射出成形機、あるいは押出機を用
いて円筒状パリソンを成形し、該パリソンをブロー成形
することでボトル、タンク等を製造する方法等が挙げら
れるが、これらの方法に限られるものではない。The method for forming a laminate in the present invention is a method for producing an unstretched film or sheet by coextrusion using a plurality of T-die extruders, and stretching the sheet in the machine direction and / or the transverse direction. A method for producing a stretched film, a method for producing cups and trays from the sheet by a deep drawing molding machine, a method for molding a cylindrical parison using a plurality of injection molding machines or extruders, and a blow molding for the parison. Thus, methods for producing bottles, tanks, and the like can be mentioned, but the method is not limited to these methods.
【0023】本発明において目的を損なわない限り、脂
肪酸アミド系、脂肪酸金属塩系、脂肪酸アマイド系化合
物等の滑剤、銅化合物、有機もしくは無機ハロゲン系化
合物、ヒンダードフェノール系、ヒンダードアミン系、
ヒドラジン系、硫黄系化合物、リン系化合物等の酸化防
止剤、ベンゾトリアゾール系等の紫外線吸収剤等の添加
剤を混合することも可能である。In the present invention, a lubricant such as a fatty acid amide compound, a fatty acid metal salt compound, a fatty acid amide compound, a copper compound, an organic or inorganic halogen compound, a hindered phenol compound, a hindered amine compound, etc.
It is also possible to mix additives such as antioxidants such as hydrazine-based compounds, sulfur-based compounds and phosphorus-based compounds, and ultraviolet absorbers such as benzotriazole-based compounds.
【0024】[0024]
【実施例】以下、実施例等により本発明を具体的に説明
する。尚、実施例等において、ポリアミド成形物の評価
方法は、下記の方法によった。 ポリアミド樹脂の相対粘度 1g/dlの96%硫酸溶液をキャノンフェンスケ粘度
計を使用して25℃における相対粘度を測定した。 分散状態 未延伸フィルムよりミクロトームにて厚さ0.1μmの
薄片を切り出し、日本電子(株)製透過型電子顕微鏡J
EM−1200EX2にて層状珪酸塩平板の分散状態を
写真撮影(倍率10万倍)した。写真画像20画面分に
ついて、隣り合う平板どうしの重心間距離をスケールに
て測定し、画像中における全平板に対して50オングス
トローム以上の重心間距離を有する平板の百分率を求め
た。The present invention will be specifically described below with reference to examples. In the examples and the like, the following method was used to evaluate a polyamide molded product. Relative Viscosity of Polyamide Resin A 1 g / dl 96% sulfuric acid solution was measured for relative viscosity at 25 ° C. using a Cannon-Fenske viscometer. Dispersion state A 0.1 μm-thick slice was cut out from the unstretched film with a microtome, and was measured using a transmission electron microscope J manufactured by JEOL Ltd.
The dispersion state of the layered silicate plate was photographed (100,000 times magnification) using EM-1200EX2. For 20 screens of the photographic image, the distance between the centers of gravity of adjacent flat plates was measured on a scale, and the percentage of flat plates having a distance between the centers of gravity of 50 Å or more with respect to all the flat plates in the image was obtained.
【0025】 透明性 日本電色工業(株)製ZE−2000を使用し、AST
M D1003に準じてフィルムの曇価(ヘイズ)を測
定した。 耐衝撃性 延伸フィルム、未延伸フィルムについてはASTM D
781に準じて測定した。測定は東洋精機(株)製PM
Iパンクチャーテスターを使用し、23℃、相対湿度5
0%の雰囲気下にて行った。 酸素透過率 延伸フィルム、未延伸フィルムについてASTM D3
985に準じて測定した。測定はモダンコントロール社
製OX−TRAN 10/50Aを使用し、23℃、相
対湿度60%の雰囲気下にて行った。Transparency Using ZE-2000 manufactured by Nippon Denshoku Industries Co., Ltd., AST
The haze of the film was measured according to MD1003. ASTM D for stretched and unstretched films
It was measured according to 781. The measurement was made by Toyo Seiki Co., Ltd. PM
23 ° C, relative humidity 5 using an I puncture tester
The test was performed in an atmosphere of 0%. Oxygen permeability ASTM D3 for stretched film and unstretched film
It was measured according to 985. The measurement was performed using OX-TRAN 10 / 50A manufactured by Modern Control Company under an atmosphere of 23 ° C. and a relative humidity of 60%.
【0026】実施例1 相対粘度が2.7であるポリアミドMXD6(三菱ガス
化学(株)製、商品名:MXナイロン6007)100
重量部と、モンモリロナイト(白石工業(株)製、商品
名:オルベン)3重量部とをドライブレンドした後、該
混合物を秤量フィーダーにて1.2kg/時間の速度で
シリンダー径20mmの二軸押出機に供給した。シリン
ダー温度270℃、スクリュー回転数100rpmの条
件で溶融混練を行った後、Tダイを通じてフィルム状物
を押出し、2.7m/分の速度で引き取りながら70℃
の冷却ロール上で固化し、厚さ50μmの未延伸フィル
ムを得た。この未延伸フィルムの各物性を表1に示す。Example 1 Polyamide MXD6 having a relative viscosity of 2.7 (manufactured by Mitsubishi Gas Chemical Company, trade name: MX nylon 6007) 100
After dry blending 3 parts by weight of montmorillonite (trade name: Orben, manufactured by Shiraishi Industry Co., Ltd.) with a weighing feeder, the mixture is biaxially extruded with a cylinder diameter of 20 mm at a rate of 1.2 kg / hour using a weighing feeder. Machine. After melt-kneading under the conditions of a cylinder temperature of 270 ° C. and a screw rotation speed of 100 rpm, a film is extruded through a T-die, and is pulled out at a speed of 2.7 m / min.
To obtain an unstretched film having a thickness of 50 μm. Table 1 shows the physical properties of the unstretched film.
【0027】実施例2 相対粘度が2.7であるポリアミドMXD6(三菱ガス
化学(株)製、商品名:MXナイロン6007)100
重量部と、モンモリロナイト(白石工業(株)製、商品
名:オルベン)3重量部とをドライブレンドした後、該
混合物を秤量フィーダーにて2.0kg/時間の速度で
シリンダー径20mmの二軸押出機に供給した。シリン
ダー温度270℃、スクリュー回転数100rpmの条
件で溶融混練を行った後、Tダイを通じてシート状物を
押出し、1.0m/分の速度で引き取りながら70℃の
冷却ロール上で固化し、厚さ300μmのシートを得
た。該シートを東洋精機(株)製二軸延伸装置で延伸温
度110℃、13倍の面積倍率で同時二軸延伸を行い、
さらに240℃で熱固定して厚さ20μmの延伸フィル
ムを得た。この延伸フィルムの各物性を表2に示す。Example 2 Polyamide MXD6 having a relative viscosity of 2.7 (manufactured by Mitsubishi Gas Chemical Company, trade name: MX nylon 6007) 100
Parts by weight and 3 parts by weight of montmorillonite (trade name: Orben, manufactured by Shiroishi Kogyo Co., Ltd.), and then the mixture was biaxially extruded with a cylinder diameter of 20 mm at a rate of 2.0 kg / hour by a weighing feeder. Machine. After melt-kneading under the conditions of a cylinder temperature of 270 ° C. and a screw rotation speed of 100 rpm, the sheet is extruded through a T-die and solidified on a 70 ° C. cooling roll while being taken off at a speed of 1.0 m / min. A 300 μm sheet was obtained. The sheet was subjected to simultaneous biaxial stretching at a stretching temperature of 110 ° C. and an area magnification of 13 times with a biaxial stretching apparatus manufactured by Toyo Seiki Co., Ltd.
Further, the film was heat-set at 240 ° C. to obtain a stretched film having a thickness of 20 μm. Table 2 shows the physical properties of the stretched film.
【0028】実施例3 ポリアミドMXD6を100重量部、モンモリロナイト
を5重量部とした以外は、実施例1と同様な方法で未延
伸フィルムを得た。この未延伸フィルムの各物性を表1
に示す。Example 3 An unstretched film was obtained in the same manner as in Example 1 except that 100 parts by weight of the polyamide MXD6 and 5 parts by weight of montmorillonite were used. Table 1 shows the properties of the unstretched film.
Shown in
【0029】実施例4 ポリアミドMXD6を100重量部、モンモリロナイト
を5重量部とした以外は、実施例2と同様な方法で延伸
フィルムを得た。この延伸フィルムの各物性を表2に示
す。Example 4 A stretched film was obtained in the same manner as in Example 2, except that 100 parts by weight of the polyamide MXD6 and 5 parts by weight of montmorillonite were used. Table 2 shows the physical properties of the stretched film.
【0030】実施例5 ポリアミドMXD6を100重量部、モンモリロナイト
を7重量部とした以外は、実施例1と同様な方法で未延
伸フィルムを得た。この未延伸フィルムの各物性を表1
に示す。Example 5 An unstretched film was obtained in the same manner as in Example 1 except that 100 parts by weight of the polyamide MXD6 and 7 parts by weight of montmorillonite were used. Table 1 shows the physical properties of the unstretched film.
Shown in
【0031】実施例6 ポリアミドMXD6を100重量部、モンモリロナイト
を7重量部とした以外は、実施例2と同様な方法で延伸
フィルムを得た。この延伸フィルムの各物性を表2に示
す。Example 6 A stretched film was obtained in the same manner as in Example 2 except that 100 parts by weight of the polyamide MXD6 and 7 parts by weight of montmorillonite were used. Table 2 shows the physical properties of the stretched film.
【0032】比較例1 モンモリロナイトを添加しなかった以外は、実施例1と
同様な方法で未延伸フィルムを得た。この未延伸フィル
ムの各物性を表1に示す。Comparative Example 1 An unstretched film was obtained in the same manner as in Example 1 except that montmorillonite was not added. Table 1 shows the physical properties of the unstretched film.
【0033】比較例2 モンモリロナイトを添加しなかった以外は、実施例2と
同様な方法で延伸フィルムを得た。この延伸フィルムの
各物性を表2に示す。Comparative Example 2 A stretched film was obtained in the same manner as in Example 2 except that montmorillonite was not added. Table 2 shows the physical properties of the stretched film.
【0034】比較例3 相対粘度が3.5であるポリアミド6(宇部興産(株)
製、商品名:宇部ナイロン1024B)100重量部
と、モンモリロナイト(白石工業(株)製、商品名:オ
ルベン)3重量部とをドライブレンドした後、該混合物
を秤量フィーダーにて1.2kg/時間の速度でシリン
ダー径20mmの二軸押出機に供給した。シリンダー温
度260℃、スクリュー回転数100rpmの条件で溶
融混練を行った後、Tダイを通じてフィルム状物を押出
し、2.7m/分の速度で引き取りながら20℃の冷却
ロール上で固化し、厚さ50μmの未延伸フィルムを得
た。この未延伸フィルムの各物性を表5に示す。Comparative Example 3 Polyamide 6 having a relative viscosity of 3.5 (Ube Industries, Ltd.)
100 parts by weight of Ube Nylon 1024B) and 3 parts by weight of montmorillonite (trade name: Orben, manufactured by Shiroishi Kogyo Co., Ltd.), and then the mixture is weighed with a weighing feeder at 1.2 kg / hour. And fed to a twin-screw extruder having a cylinder diameter of 20 mm. After melt-kneading at a cylinder temperature of 260 ° C. and a screw rotation speed of 100 rpm, the film is extruded through a T-die, solidified on a cooling roll at 20 ° C. while being drawn at a speed of 2.7 m / min. An unstretched film of 50 μm was obtained. Table 5 shows the physical properties of the unstretched film.
【0035】比較例4 相対粘度が3.5であるポリアミド6(宇部興産(株)
製、商品名:宇部ナイロン1024B)100重量部
と、モンモリロナイト(白石工業(株)製、商品名:オ
ルベン)3重量部とをドライブレンドした後、該混合物
を秤量フィーダーにて2.0kg/時間の速度でシリン
ダー径20mmの二軸押出機に供給した。シリンダー温
度260℃、スクリュー回転数100rpmの条件で溶
融混練を行った後、Tダイを通じてシート状物を押出
し、1.0m/分の速度で引き取りながら20℃の冷却
ロール上で固化し、厚さ300μmのシートを得た。該
シートを東洋精機(株)製二軸延伸装置で延伸温度50
〜80℃、4〜6倍の面積倍率で同時二軸延伸を試みた
が、破断により延伸不可能であった。Comparative Example 4 Polyamide 6 having a relative viscosity of 3.5 (Ube Industries, Ltd.)
100 parts by weight of Ube Nylon 1024B) and 3 parts by weight of montmorillonite (trade name: Orben, manufactured by Shiraishi Industry Co., Ltd.), and then the mixture is weighed with a weighing feeder at 2.0 kg / hour. And fed to a twin-screw extruder having a cylinder diameter of 20 mm. After melt-kneading under the conditions of a cylinder temperature of 260 ° C. and a screw rotation speed of 100 rpm, the sheet is extruded through a T-die and solidified on a cooling roll at 20 ° C. while being drawn at a speed of 1.0 m / min. A 300 μm sheet was obtained. The sheet was stretched at a stretching temperature of 50 using a biaxial stretching apparatus manufactured by Toyo Seiki Co., Ltd.
Simultaneous biaxial stretching was attempted at an area magnification of 4 to 6 times at 8080 ° C., but stretching was not possible due to rupture.
【0036】比較例5 モンモリロナイトの添加量を0.05重量部とした以外
は、実施例1と同様な方法で未延伸フィルムを得た。こ
の未延伸フィルムの各物性を表5に示す。Comparative Example 5 An unstretched film was obtained in the same manner as in Example 1, except that the amount of montmorillonite was changed to 0.05 part by weight. Table 5 shows the physical properties of the unstretched film.
【0037】比較例6 モンモリロナイトの添加量を0.05重量部とした以外
は、実施例2と同様な方法で延伸フィルムを得た。この
延伸フィルムの各物性を表4に示す。Comparative Example 6 A stretched film was obtained in the same manner as in Example 2 except that the amount of montmorillonite was changed to 0.05 part by weight. Table 4 shows the physical properties of the stretched film.
【0038】比較例7 モンモリロナイトの添加量を15重量部とした以外は、
実施例1と同様な方法で未延伸フィルムを得た。この未
延伸フィルムの各物性を表3に示す。Comparative Example 7 Except that the amount of montmorillonite was changed to 15 parts by weight,
An unstretched film was obtained in the same manner as in Example 1. Table 3 shows the physical properties of the unstretched film.
【0039】比較例8 モンモリロナイトの添加量を15重量部とした以外は、
実施例2と同様な方法で延伸フィルムを得た。この延伸
フィルムの各物性を表4に示す。Comparative Example 8 Except that the amount of montmorillonite was changed to 15 parts by weight,
A stretched film was obtained in the same manner as in Example 2. Table 4 shows the physical properties of the stretched film.
【0040】[0040]
【発明の効果】本発明のポリアミド成形物は、透明性、
ガスバリヤー性、機械的性能に優れるため、食品、飲
料、薬品、電子部品等の包装資材として有用である。The polyamide molded product of the present invention has transparency,
Since it has excellent gas barrier properties and mechanical performance, it is useful as a packaging material for foods, beverages, drugs, electronic components, and the like.
【0041】[0041]
【表1】実施例・比較例番号 実施例1 実施例3 実施例5 比較例1 成分 樹脂 種類 N-MXD6 N-MXD6 N-MXD6 N-MXD6 相対粘度 2.7 2.7 2.7 2.7 配合量(重量部) 100 100 100 100 モンモリロナイト(重量部) 3 5 7 0 評価結果 分散状態(%) 98 85 70 − ヘイズ(%) 4.0 4.1 4.3 1.4 衝撃強度(kgf・cm) 1.6 1.5 1.5 1.5 酸素透過係数(cc-mm/m2-day-atm) 0.06 0.05 0.05 0.09 [Table 1] Example / Comparative Example No. Example 1 Example 3 Example 5 Comparative Example 1 Component Resin Type N-MXD6 N-MXD6 N-MXD6 N-MXD6 Relative viscosity 2.7 2.7 2.7 2.7 Blending amount (parts by weight) 100 100 100 100 Montmorillonite (parts by weight) 3 5 7 0 Evaluation result Dispersion state (%) 98 85 70 − Haze (%) 4.0 4.1 4.3 1.4 Impact strength (kgf · cm) 1.6 1.5 1.5 1.5 Oxygen transmission coefficient (cc-mm / m2-day-atm) 0.06 0.05 0.05 0.09
【0042】[0042]
【表2】実施例・比較例番号 実施例2 実施例4 実施例6 比較例2 成分 樹脂 種類 N-MXD6 N-MXD6 N-MXD6 N-MXD6 相対粘度 2.7 2.7 2.7 2.7 配合量(重量部) 100 100 100 100 モンモリロナイト(重量部) 3 5 7 0 評価結果 ヘイズ(%) 12 12 12 1.6 衝撃強度(kgf・cm) 6.0 5.8 5.7 8.1 酸素透過係数(cc-mm/m2-day-atm) 0.04 0.03 0.03 0.06 [Table 2] Example / Comparative Example No. Example 2 Example 4 Example 6 Comparative Example 2 Component Resin Type N-MXD6 N-MXD6 N-MXD6 N-MXD6 Relative viscosity 2.7 2.7 2.7 2.7 Compounding amount (parts by weight) 100 100 100 100 Montmorillonite (parts by weight) 3 5 7 0 Evaluation result Haze (%) 12 12 12 1.6 Impact strength (kgf · cm) 6.0 5.8 5.7 8.1 Oxygen permeability coefficient (cc-mm / m2-day-atm) 0.04 0.03 0.03 0.06
【0043】[0043]
【表3】比較例番号 比較例3 比較例5 比較例7 成分 樹脂 種類 N-6 N-MXD6 N-MXD6 相対粘度 3.5 2.7 2.7 配合量(重量部) 100 100 100 モンモリロナイト(重量部) 3 0.05 15 評価結果 分散状態(%) 99 99 45 ヘイズ(%) 4.0 1.5 13 衝撃強度(kgf・cm) 1.6 1.5 1.5 酸素透過係数(cc-mm/m2-day-atm) 0.07 0.09 0.09 [Table 3] Comparative Example No. Comparative Example 3 Comparative Example 5 Comparative Example 7 Component Resin Type N-6 N-MXD6 N-MXD6 Relative viscosity 3.5 2.7 2.7 Compounding amount (parts by weight) 100 100 100 Montmorillonite (parts by weight) 3 0.05 15 Evaluation results Dispersion state (%) 99 99 45 Haze (%) 4.0 1.5 13 Impact strength (kgf · cm) 1.6 1.5 1.5 Oxygen transmission coefficient (cc-mm / m2-day-atm) 0.07 0.09 0.09
【0044】[0044]
【表4】比較例番号 比較例4 比較例6 比較例8 成分 樹脂 種類 N-6 N-MXD6 N-MXD6 相対粘度 3.5 2.7 2.7 配合量(重量部) 100 100 100 モンモリロナイト(重量部) 3 0.05 15 評価結果 ヘイズ(%) − 2.0 20 衝撃強度(kgf・cm) − 7.8 5.7 酸素透過係数(cc-mm/m2-day-atm) − 0.06 0.06 [Table 4] Comparative Example No. Comparative Example 4 Comparative Example 6 Comparative Example 8 Component Resin Type N-6 N-MXD6 N-MXD6 Relative viscosity 3.5 2.7 2.7 Blending amount (parts by weight) 100 100 100 Montmorillonite (parts by weight) 3 0.05 15 Evaluation result Haze (%)-2.0 20 Impact strength (kgfcm)-7.8 5.7 Oxygen permeability coefficient (cc-mm / m2-day-atm)-0.06 0.06
───────────────────────────────────────────────────── フロントページの続き (51)Int.Cl.7 識別記号 FI テーマコート゛(参考) C08K 3/34 C08K 3/34 // B29K 77:00 B29L 7:00 9:00 22:00 Fターム(参考) 4F071 AA55 AA88 AB30 AH04 AH05 BA01 BB06 BB07 BB08 BC01 BC04 4F100 AC04A AE08A AE09A AK01B AK01C AK46A BA01 BA03 BA07 BA10B BA10C EJ37A GB15 GB16A JA06A JB16C JD02 JK00 JN01 YY00A 4F210 AA29 AB16 AG01 AG03 AH55 QC01 QC05 QG01 QG15 QG18 4J002 CL031 DJ006 DJ036 DJ056 FA016 FD070 GG01 GG02──────────────────────────────────────────────────続 き Continued on the front page (51) Int.Cl. 7 Identification symbol FI Theme coat ゛ (Reference) C08K 3/34 C08K 3/34 // B29K 77:00 B29L 7:00 9:00 22:00 F term ( Reference) 4F071 AA55 AA88 AB30 AH04 AH05 BA01 BB06 BB07 BB08 BC01 BC04 4F100 AC04A AE08A AE09A AK01B AK01C AK46A BA01 BA03 BA07 BA10B BA10C EJ37A GB15 GB16A JA06A JB16C JD02 JK01 J01A01 DJ056 FA016 FD070 GG01 GG02
Claims (6)
ンを70モル%以上含むジアミンと、ジカルボン酸成分
中に炭素数4〜20のα,ω−直鎖脂肪族ジカルボン酸
を70モル%以上含むジカルボン酸とを重縮合したポリ
アミド樹脂(A)100重量部に対し、層状珪酸塩
(B)を0.1〜10重量部配合して得られる樹脂組成
物(C)を成形したポリアミド成形物であって、層状珪
酸塩が溶融混練によりポリアミド樹脂中に微分散されて
いることを特徴とするポリアミド成形物。1. A diamine containing at least 70 mol% of metaxylylenediamine in a diamine component, and a dicarboxylic acid containing at least 70 mol% of an α, ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms in a dicarboxylic acid component. A polyamide molded product obtained by molding a resin composition (C) obtained by mixing 0.1 to 10 parts by weight of a layered silicate (B) with 100 parts by weight of a polyamide resin (A) polycondensed with an acid. Characterized in that the layered silicate is finely dispersed in the polyamide resin by melt-kneading.
2.2〜4.0である請求項1に記載のポリアミド成形
物。2. The polyamide resin (A) has a relative viscosity of:
The polyamide molded product according to claim 1, wherein the ratio is 2.2 to 4.0.
ト、又は中空容器である請求項1記載のポリアミド成形
物。3. The polyamide molding according to claim 1, wherein the polyamide molding is a film, a sheet, or a hollow container.
16倍に延伸された延伸フィルムである請求項1記載の
ポリアミド成形物。4. The polyamide molded product has an area stretching ratio of 4 to 4.
The polyamide molded product according to claim 1, which is a stretched film stretched 16 times.
30倍に延伸ブロー成形されたボトルである請求項1記
載のポリアミド成形物。5. The polyamide molded product has an area stretching ratio of 1 to 5.
The polyamide molded product according to claim 1, which is a bottle stretch-blown by 30 times.
からなる少なくとも一つの層と、他の熱可塑性樹脂から
なる少なくとも一つの層が接合してなる多層フィルム、
多層シート、または多層容器である請求項1記載のポリ
アミド成形物。6. The polyamide molded product is a resin composition (C).
At least one layer consisting of, and a multilayer film formed by joining at least one layer made of another thermoplastic resin,
The polyamide molded product according to claim 1, which is a multilayer sheet or a multilayer container.
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| JP10003999A JP2000290500A (en) | 1999-04-07 | 1999-04-07 | Polyamide molding |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| JP10003999A JP2000290500A (en) | 1999-04-07 | 1999-04-07 | Polyamide molding |
Publications (1)
| Publication Number | Publication Date |
|---|---|
| JP2000290500A true JP2000290500A (en) | 2000-10-17 |
Family
ID=14263392
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP10003999A Pending JP2000290500A (en) | 1999-04-07 | 1999-04-07 | Polyamide molding |
Country Status (1)
| Country | Link |
|---|---|
| JP (1) | JP2000290500A (en) |
Cited By (8)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2002129012A (en) * | 2000-10-26 | 2002-05-09 | Unitika Ltd | Polyamide resin composition and method for producing the same |
| JP2005206806A (en) * | 2003-12-26 | 2005-08-04 | Mitsubishi Gas Chem Co Inc | Thermoplastic resin composition having excellent barrier properties and molded article comprising the same |
| JP2006516670A (en) * | 2003-01-31 | 2006-07-06 | エンメ エ ジ・ポリメリ・イタリア・ソチエタ・ペル・アツィオーニ | Articles containing light absorbing compositions that mask visual haze and related methods |
| JP2006241299A (en) * | 2005-03-03 | 2006-09-14 | Mitsubishi Gas Chem Co Inc | Thermoplastic resin composition having excellent barrier properties and molded article comprising the same |
| US7259196B2 (en) | 2002-07-23 | 2007-08-21 | Kaneka Corporation | Polyamide resin composition and process for producing the same |
| WO2020059749A1 (en) * | 2018-09-21 | 2020-03-26 | 三菱瓦斯化学株式会社 | Stretched body, pet bottle and container manufacturing method |
| EP3854855A4 (en) * | 2018-09-21 | 2021-11-03 | Mitsubishi Gas Chemical Company, Inc. | COMPOSITION OF RESIN, MOLDED BODY, AND ASSOCIATED APPLICATION |
| JP2024072876A (en) * | 2020-06-10 | 2024-05-28 | 三菱瓦斯化学株式会社 | Method for producing resin composition, composition and pellets |
-
1999
- 1999-04-07 JP JP10003999A patent/JP2000290500A/en active Pending
Cited By (19)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2002129012A (en) * | 2000-10-26 | 2002-05-09 | Unitika Ltd | Polyamide resin composition and method for producing the same |
| US7259196B2 (en) | 2002-07-23 | 2007-08-21 | Kaneka Corporation | Polyamide resin composition and process for producing the same |
| JP2006516670A (en) * | 2003-01-31 | 2006-07-06 | エンメ エ ジ・ポリメリ・イタリア・ソチエタ・ペル・アツィオーニ | Articles containing light absorbing compositions that mask visual haze and related methods |
| JP2011038109A (en) * | 2003-01-31 | 2011-02-24 | M & G Polimeri Italia Spa | Product comprising light absorbent composition to mask visual haze and related method |
| JP2005206806A (en) * | 2003-12-26 | 2005-08-04 | Mitsubishi Gas Chem Co Inc | Thermoplastic resin composition having excellent barrier properties and molded article comprising the same |
| JP2006241299A (en) * | 2005-03-03 | 2006-09-14 | Mitsubishi Gas Chem Co Inc | Thermoplastic resin composition having excellent barrier properties and molded article comprising the same |
| KR20210062001A (en) * | 2018-09-21 | 2021-05-28 | 미쯔비시 가스 케미칼 컴파니, 인코포레이티드 | Manufacturing method of elongated body, PET bottle and container |
| CN112771117A (en) * | 2018-09-21 | 2021-05-07 | 三菱瓦斯化学株式会社 | Stretched body, plastic bottle, and method for producing container |
| WO2020059749A1 (en) * | 2018-09-21 | 2020-03-26 | 三菱瓦斯化学株式会社 | Stretched body, pet bottle and container manufacturing method |
| JPWO2020059749A1 (en) * | 2018-09-21 | 2021-09-30 | 三菱瓦斯化学株式会社 | Method for manufacturing stretched bodies, PET bottles and containers |
| EP3854855A4 (en) * | 2018-09-21 | 2021-11-03 | Mitsubishi Gas Chemical Company, Inc. | COMPOSITION OF RESIN, MOLDED BODY, AND ASSOCIATED APPLICATION |
| EP3854852A4 (en) * | 2018-09-21 | 2021-11-17 | Mitsubishi Gas Chemical Company, Inc. | STRETCHED BODY, PET BOTTLE AND CONTAINER MANUFACTURING PROCESS |
| CN112771117B (en) * | 2018-09-21 | 2023-06-02 | 三菱瓦斯化学株式会社 | Method for manufacturing stretched body, plastic bottle and container |
| JP7351308B2 (en) | 2018-09-21 | 2023-09-27 | 三菱瓦斯化学株式会社 | Method for producing stretched bodies, plastic bottles and containers |
| US11981809B2 (en) | 2018-09-21 | 2024-05-14 | Mitsubishi Gas Chemical Company, Inc. | Stretched body, PET bottle, and method for producing container |
| KR102796221B1 (en) | 2018-09-21 | 2025-04-16 | 미쯔비시 가스 케미칼 컴파니, 인코포레이티드 | Method for manufacturing elongated body, PET bottle and container |
| US12378358B2 (en) * | 2018-09-21 | 2025-08-05 | Mitsubishi Gas Chemical Company, Inc. | Resin composition, molded body, and their application |
| JP2024072876A (en) * | 2020-06-10 | 2024-05-28 | 三菱瓦斯化学株式会社 | Method for producing resin composition, composition and pellets |
| JP7790457B2 (en) | 2020-06-10 | 2025-12-23 | 三菱瓦斯化学株式会社 | Method for producing resin composition, composition and pellets |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| EP0475720B1 (en) | Polyamide resin composition and film therefrom | |
| JP5949546B2 (en) | Polyamide resin composition | |
| CN111094456B (en) | Resin composition, molded article, and film | |
| TWI791499B (en) | Resin composition, molded product, film and multilayer film | |
| JPWO2011145498A1 (en) | Polyamide resin composition | |
| TWI492963B (en) | Heat-shrinkable film | |
| EP1156073B1 (en) | Shaped article of polyamide resin and production thereof | |
| CN100436513C (en) | Biaxially stretched film and production method thereof | |
| JPS6024814B2 (en) | resin composition | |
| AU2002301517B2 (en) | Polyamide Resin Composition | |
| WO2009154263A1 (en) | Film for wrapping goods having protrusions | |
| TW201910134A (en) | Easily-torn film, multilayer film, packaging material, and container | |
| US12247108B2 (en) | Stretched film, packaging material, and method for producing stretched film | |
| JP7351308B2 (en) | Method for producing stretched bodies, plastic bottles and containers | |
| JP2002038006A (en) | Polyamide resin composition and method for producing the same | |
| JP4207526B2 (en) | Polyamide resin composition | |
| JPS62127346A (en) | Polyamide composition | |
| JP2001354222A (en) | Multi-layer container | |
| JP2003155359A (en) | Biaxially stretched polyamide film | |
| JP2004161326A (en) | Paper container | |
| JP2005146207A (en) | Stretched film | |
| JP3537604B2 (en) | Multilayer film | |
| JP2023088383A (en) | Resin composition, film, multilayer film, packaging material, and method for producing film | |
| JP4535223B2 (en) | Polyamide composite material and method for producing the same | |
| JP4474807B2 (en) | Polyamide resin composition for film |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| A621 | Written request for application examination |
Free format text: JAPANESE INTERMEDIATE CODE: A621 Effective date: 20060328 |
|
| A131 | Notification of reasons for refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A131 Effective date: 20090128 |
|
| A02 | Decision of refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A02 Effective date: 20090624 |